2018 IEEE International Conference on Electrical Systems for Aircraft, Railway, Ship Propulsion and Road Vehicles &Amp; Interna 2018
DOI: 10.1109/esars-itec.2018.8607585
|View full text |Cite
|
Sign up to set email alerts
|

Model Predictive Control Based PID Controller for PMSM for Propulsion Systems

Abstract: Model Predictive Control (MPC) is one of the most suitable controllers for industrial applications, especially for constrained systems. However, it requires high computational burden, which is considered as the main drawback. Proportional Integral Derivative (PID) controller is the most widely used controller in particular for Single Input Single Output (SISO) system and for cascaded control loops, but it is difficult to be tuned especially for a constrained system. Therefore, a combination of PID and MPC is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The controller gains in (3) are tuned based on the pole zero cancelation method where they are selected according to (4) and (5) [7,8], where L' and r' represent the machine nominal parameters in Table 1. Note that their values might be different from the actual machine parameters L and r.…”
Section: A Conventional Pi CC With Pole/zero Cancelation Methods (1 Smentioning
confidence: 99%
See 1 more Smart Citation
“…The controller gains in (3) are tuned based on the pole zero cancelation method where they are selected according to (4) and (5) [7,8], where L' and r' represent the machine nominal parameters in Table 1. Note that their values might be different from the actual machine parameters L and r.…”
Section: A Conventional Pi CC With Pole/zero Cancelation Methods (1 Smentioning
confidence: 99%
“…It can be argued that the current control loop has a major effect on the overall system performance [1]. Therefore, many studies that investigate various current control schemes are reported in [2][3][4][5]. The hysteresis controller, for instance, can achieve instantaneous tracking of the reference.…”
Section: Introductionmentioning
confidence: 99%
“…receding horizon control), an operational power management could use a two-stage control methodology consisting of some form of EMS optimisation and a continuously modulated mechanism (e.g. PID, predictive control) in order to exploit pre-driving and on-line power allocation [22], [40], [64]. In the former stage (pre-driving), the system could use a ground movement forecast [4], [65], [66] (e.g.…”
Section: Applications On Real Time Operational Taxiingmentioning
confidence: 99%
“…MPC has been applied successfully for different applications to enhance the performance and robustness. It has been applied for different electrical machines including PMSM [27], [9]. MPC can replace the PI controllers' loops to obtain the FOC strategy taking into consideration the system constraints through the MPC cost function.…”
Section: Model Predictive Controlmentioning
confidence: 99%
“…The MPC cost function is given by [27,29]: 24) subject to a discrete state-space model in ( 22) and ( 23), where ( ) 3 * 1 = ( ) 3 * 1 − ( ) 3 * 1 is the error, ( ) 3 * 1 is the system output, ( ) 3 * 1 is the reference input, ( ) 2 * 1 is the system control input, Q( ) 3 * 3 and R( ) 2 * 2 are weighting matrices, ny is the prediction horizon value and nu is the control horizon value. The model could be used recursively to find the predictions over the prediction horizon ny as follows:…”
Section: Model Predictive Controlmentioning
confidence: 99%